2017
DOI: 10.1177/1368430216682353
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Muslim identity: Opinion-based groups in the Gezi Park protest

Abstract: Media depicted Turkish Gezi Park protests as a clash between secularists and Islamists within a majority-Muslim country. Extending a social identity approach to protests, this study aims (a) to distinguish the protest participants in terms of their opinion-based group memberships, (b) to investigate how their religious identification and their group membership were associated with democratic attitudes. Six hundred and fifty highly educated urban young adult participants were surveyed during the protest. Latent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 52 publications
2
42
1
Order By: Relevance
“…While "private" Muslims are strongly attached to their Muslim identity with low religious practice, strict and selective Muslims have strong religious attachments, and strong or moderate religious practices, respectively. We tentatively expect to find "strict" and "moderate/secular" types in the current study, in line with the conservative versus secular divide among Turkish-Muslims in Turkey (Baysu & Phalet, 2017). Moreover, the present study only includes measures of religious practice, making it unlikely to find a "private" Muslim with high attachment and no religious practice (Phalet et al, 2012).…”
Section: Religious Identity Content As Muslimsupporting
confidence: 53%
See 2 more Smart Citations
“…While "private" Muslims are strongly attached to their Muslim identity with low religious practice, strict and selective Muslims have strong religious attachments, and strong or moderate religious practices, respectively. We tentatively expect to find "strict" and "moderate/secular" types in the current study, in line with the conservative versus secular divide among Turkish-Muslims in Turkey (Baysu & Phalet, 2017). Moreover, the present study only includes measures of religious practice, making it unlikely to find a "private" Muslim with high attachment and no religious practice (Phalet et al, 2012).…”
Section: Religious Identity Content As Muslimsupporting
confidence: 53%
“…For instance, in the United States, the liberal-conservative ideological dimension seems to be more salient, and in turn, it predicts voting (Jacoby, 2010). From the perspective of cleavage theory (Lipset & Rokkan, 1967), religion is a salient social-political cleavage among voters in Turkey (Baysu & Phalet, 2017;Çarkoğlu, 2007;Kalaycıoglu, 1994). Secularist versus religious/pro-Islamist cleavage overlaps with Mardin's (1973) traditional center (the secularist) versus periphery (the religious) distinction in the formation of Turkish politics (Çarkoğlu, 2007;Kalaycıoglu, 1994).…”
Section: Left-right Ideologymentioning
confidence: 99%
See 1 more Smart Citation
“…According to the specific mediating effect tests, we found that group efficacy was a significant mediator of the relationship between religious identity and collective action intention (i.e., support for Hypothesis 2b). Our findings contribute to the explanation that religious identity predicts the desire to engage in collective action (Baysu & Phalet, 2017). We suspect that the source of group efficacy pertaining to the Palestinian issue is largely attributable to religious identity, which helps explain the reason Muslim religious identity -through the mediating effect of group efficacy -has a stronger effect on collective action intention.…”
Section: Discussionmentioning
confidence: 53%
“…Religious identity is also manifested as either normative (peaceful) or nonnormative (violent) collective action depending on the purpose of the action, its positive acceptance, and threats to identity (Phalet, Baysu, & Verkuyten, 2010). Another study dmeonstrated that although the identification of Muslims did not play a role in supporting democracy during the Gezi Turkey protest in 2013, identification as a Muslim did indicate a slightly different pattern in adopted political attitudes (i.e., secular, liberal, conservative, or moderate) (Baysu & Phalet, 2017).…”
Section: Introductionmentioning
confidence: 99%